COMPARATIVE STUDY OF STREET NAMES ING ENGLISH AND UZBEK LANGUAGES - Saparova, Pokiza Mamatqul qizi (Educational Research in Universal Sciences, 2023)
This article presents a comparative analysis of street names in English and Uzbek languages, exploring historical, cultural, linguistic, and sociolinguistic influences. The study aims to uncover similarities and differences in street naming conventions, and it discusses the significance of street names as linguistic and cultural artifacts.